Total Plate Count of Milk from Dairy Cooperatives in Yogyakarta and East Java - Monica Septiani; Yatri Drastini (Jurnal Sain Veteriner, 2014)
Most of the local populations in Indonesia, especially in Sleman, Yogyakarta and Tulungagung, East Java consume cow milk. Cow milk is more widely consumed than that of horse or goat because of the people  habit and the raw milk is more easily found in the market. The majority of people consume milk without knowing the number of bacteria contained and neither the presence nor absence of harmful bacteria in the milk consumed. This study aimed to identify the total number of bacteria in several dairy cooperatives in Sleman, Yogyakarta and Tulungagung, East Java. Milk samples were taken from two tanks in Koperasi Sarono Makmur (KSM), three tanks (were taken four times, once a week) in Koperasi Warga Mulya (KWM) Sleman, Yogyakarta, and two tanks (twice in the morning and once in the evening) in Koperasi Unit Tani Ternak (KUTT) Tulungagung, East Java. Milk from each tank were taken 500 mL and put into the cooler that was given ice cubes. Then the samples to be tested for total bacteria from each tank with plate count agar medium. The number of samples was 19. Milk samples were statistically analyzed with one way ANOVA. The results showed that the total number of bacteria of milk of KSM is 1.0 x 106 CFU/mL, KWM 3.6 x 106 CFU/mL, whereas cow's milk KUTT 4.0 x 106 CFU/mL. The average total number of bacteria of KWM and KUTT exceeds the requirements of the Indonesian National Standard (SNI) 01-3141-1998 (1,0 x 106 CFU/mL).